2013
DOI: 10.1016/j.dhjo.2013.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Childhood vision impairment, hearing loss and co-occurring autism spectrum disorder

Abstract: Background Limited population-based data on prevalence of childhood vision impairment (VI) and hearing loss (HL), and their co-occurrence with autism spectrum disorder (ASD) exists. Objective To examine prevalence and characteristics of VI, HL and co-occurring ASD among 8-year-olds in metropolitan Atlanta 2000–2008. Methods We used data from the population-based Metropolitan Atlanta Developmental Disabilities Surveillance Program. Prevalence, birth and parental characteristics, presence and severity of oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 37 publications
(41 reference statements)
2
55
0
Order By: Relevance
“…These studies confirm the existence of a greater ASD risk in hearing-impaired subjects [7,8,32,39,40], suggesting that the social interaction difficulties suffered by these people are even worse because of sensory deprivation [8]. This situation underlines the need to identify cases earlier because these subjects require different and additional care [40]. Some studies suggest that there is a greater risk of middle ear problems in ASD subjects [8,42].…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…These studies confirm the existence of a greater ASD risk in hearing-impaired subjects [7,8,32,39,40], suggesting that the social interaction difficulties suffered by these people are even worse because of sensory deprivation [8]. This situation underlines the need to identify cases earlier because these subjects require different and additional care [40]. Some studies suggest that there is a greater risk of middle ear problems in ASD subjects [8,42].…”
Section: Discussionsupporting
confidence: 73%
“…We have found some studies that address the comorbidity of ASD and deafness [7,8,32,40,41], which was detected in a small portion of the sample in the present study. These studies confirm the existence of a greater ASD risk in hearing-impaired subjects [7,8,32,39,40], suggesting that the social interaction difficulties suffered by these people are even worse because of sensory deprivation [8].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Different research studies showed that when disabled adults seek that analogue assistive technologies, such as examination aid, prostheses and wheelchairs, come to symbolise an identity that marks them as different, they reject the assistive technology [5,6]. While these studies indicated that the use of analogue assistive technologies by adults the research was focused on young people amalgamation of information and communication technologies and ICT assistive technology in order to show which technology transmits the most significant symbols in their daily lives [7,8]. The important objective of the visual assistive technology for computer and other technologies have provided best possible vision improvement or sight exchange device.…”
mentioning
confidence: 99%